2011
DOI: 10.1007/s00442-011-2112-z
|View full text |Cite
|
Sign up to set email alerts
|

Trait-based community assembly of understory palms along a soil nutrient gradient in a lower montane tropical forest

Abstract: Two opposing niche processes have been shown to shape the relationship between ecological traits and species distribution patterns: habitat filtering and competitive exclusion. Habitat filtering is expected to select for similar traits among coexisting species that share similar habitat conditions, whereas competitive exclusion is expected to limit the ecological similarity of coexisting species leading to trait differentiation. Here, we explore how functional traits vary among 19 understory palm species that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 65 publications
0
51
0
2
Order By: Relevance
“…According to community assembly theory, species turnover within communities across abiotic gradients is primarily derived from the adaptive differences of each species to the external habitat (Cornwell and Ackerly, 2009;Andersen et al, 2012). In this study, on one side of the environmental gradient from south to north, woody plant species with evergreen broadleaves (low SLA but high LDMC) dominated in the tropic regions characterized by hot, humid, and infertile habitats, accompanied by low SLA CWM and high LDMC CWM .…”
Section: Latitudinal Variation In Community-level Leaf Traits and Thementioning
confidence: 92%
“…According to community assembly theory, species turnover within communities across abiotic gradients is primarily derived from the adaptive differences of each species to the external habitat (Cornwell and Ackerly, 2009;Andersen et al, 2012). In this study, on one side of the environmental gradient from south to north, woody plant species with evergreen broadleaves (low SLA but high LDMC) dominated in the tropic regions characterized by hot, humid, and infertile habitats, accompanied by low SLA CWM and high LDMC CWM .…”
Section: Latitudinal Variation In Community-level Leaf Traits and Thementioning
confidence: 92%
“…1). Hornito and Alto Frio typically have 1-2 months per year with <100 mm of precipitation; in contrast, no months with <100 mm of rainfall have been recorded over the 7-year period for which records are available at Honda A and Honda B (Andersen et al 2012; J. Dalling unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…1 Andersen et al (2010) Mycorrhiza In addition to differences in rainfall, these sites differ markedly in soil characteristics, with contrasting pH, N, P, and base cation availability (Table 1). These distinctive soil traits are related to underlying geology: low-fertility Ultisols at Honda A and Honda B are derived from rhyolite, whereas high fertility soils at Hornito (Ultisol) and Alto Frio (Inceptisol) are derived from dacite and andesite (Andersen et al 2012;B. Turner unpublished data).…”
Section: Hornitomentioning
confidence: 99%
“…Preference for different N-forms has not, however, always been linked to plant species' distributions (e.g., Aanderud and Bledsoe 2009;von Felten et al 2009). Although the distributions of understory palm species along a soil gradient in a Panamanian tropical forest were more closely linked to nutrient availability than to either rainfall or light (Andersen et al 2012), no species showed a significant preference for forms of N that were most abundant in the soils in which they grew. Instead, species' distributions were related to total N-uptake rates (Andersen and Turner 2013).…”
Section: Introductionmentioning
confidence: 94%
“…However, if specialization on particular forms enables dramatically more efficient uptake, then betweenspecies differences in N uptake strategies may lead to niche partitioning across edaphic gradients varying in supply rates of N forms, which would facilitate species coexistence (Tilman 1982). Work to date testing this hypothesis in tropical forests has focused on relating tree species' traits (e.g., foliar N and d 15 N, nitrate reductase activity) to the availability and isotopic signature of different N-forms (Aidar et al 2003;Schimann et al 2008;Andersen et al 2012) and rates of microbial transformations of N in soil (Schimann et al 2008;Andersen et al 2012). Few studies have directly quantified differences among tropical tree species in the capacity to take up different forms of N, with the exception of Andersen and Turner (2013), who limited their work to understory palms.…”
Section: Introductionmentioning
confidence: 99%